SUSTAINABLE FINANCIAL LITERACY POLICY IN BREAKING THE CHAIN OF DEBT AND RECEIVABLES IN HOUSEHOLDS - FADLI, AHMAD; MASRUROH, NIKMATUL; FAWAID, YAZIDUL; SHAHRIN, ATTORI ALFI (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The purpose of this research, firstly; explore the practices of accounts payable and receivable that occur in households, secondly; the formulation a sustainable financial literacy policy through digital applications and cooperative innovation and changing